International Lifestyle Migration in the Andes of Ecuador: How Migrants from the USA Perform Privilege, Import Rurality and Evaluate Their Impact on Local Community - Kordel, Stefan; Pohle, Perdita (Sociologia Ruralis, 2016)
Using the example of Vilcabamba in Ecuador, this article explores the ways that migrants from the USA materialise their quest for better lives by relocating to smallcommunities in the Global South. Taking a lifestyle migration approach, we explore the ways migrants interpret and perform rurality in their post-migration lives according to their economic and symbolically privileged status. Empirical data gathered from biographical narrative interviews with immigrants and guideline-based interviews with experts show that migrants construct their own, mostly idealised, meanings of rurality; for instance, through the enactment of a healthy way of life close to nature, and social community spirit. Performing their privileged status through everyday practices, lifestyle migrants transfer their mostly Western understandings of rurality, derived from notions of the rural idyll, to other socio-cultural settings. Consequently, they foster various transformations of local society, economy and public space. At the same time, however, via critical self-reﬂection, they exhibit an ambivalent attitude to these transformations.
Keywords: lifestyle migration; privilege; rural idyll; rural gentrification; Ecuador